Risk of Second Cancers in Merkel Cell Carcinoma: A Meta-Analysis of Population Based Cohort Studies. (10th December 2014) - Saxena, Anshul; Rubens, Muni; Ramamoorthy, Venkataraghavan; Khan, Hafiz
Abstract : The risk of second cancers in Merkel cell carcinoma (MCC) remains uncertain since risk estimates vary worldwide. The global MCC population is growing and there is a demand for better knowledge of prognosis of this disease. The Cochrane Database of Systematic Reviews, MEDLINE, and EMBASE search engines were searched for the relevant literature between January 1999 and September 2014 by use of explicit search criteria. The main outcome was second malignancies associated with MCC patients measured by standardized incidence ratios (SIRs) or other estimates of risks. Five papers fulfilled the inclusion criteria and reported SIRs of second cancer in MCC which varied from 1.07 to 2.80. Performing meta-analysis using random effects model revealed that there was an increased risk for second malignancies due to MCC (SIR, 1.52; 95% CI, 1.10–2.11). There was a significant increase in risk for malignant melanoma (SIR, 3.09; 95% CI, 2.02–4.73) as compared to all common second malignancies among the studies. Updated knowledge about risk of second malignancies in MCC will help in better assessment of the disease prognosis and will help in optimizing the medical and surgical treatment, radiotherapy, follow-up, and surveillance procedures.